Deteksi Bakteri Penyebab CVPD pada Jeruk Menggunakan DNA Asal Tulang Daun - Rustiani, Ummu Salamah; Endah, Ariningsih Salji; Nurjanah, Nurjanah; Prasetiawan, Andi; Nurmaida, Nurmaida (Jurnal Fitopatologi Indonesia, 2015)
A method for identification of the causal bacteria of citrus vein phloem degeneration (CVPD) based on polymerase chain reaction (PCR) technique using template DNA extracted from leaf midrib of citrus has been implemented routinely. The method has not been validated, therefore it is necessary to validate the method to confirm that the method fit for its intended use. Leaf samples showing chlorotic symptom was obtained from Bogor and Bekasi, West Java and used for test samples. These samples was differentiated into 2 groups, i.e. leaf midrib and leaf mesophyll. Validation test involved homogenicity, and reproducibility test; each test was replicated 2 times. The test showed that using leaf midrib gave better result for detection of bacteria causing CVPD disease than using leaf mesophyll. Therefore, this method is recommended as routine detection method for bacteria causing CVPD disease.